The Effects of Monetary Policy: Theory with Measured Expectations - Christopher Roth; Mirko Wiederholt; Johannes Wohlfart (Center for Economic Studies and ifo Institute (CESifo), 2023)
We study the effects of monetary policy on aggregate consumption combining a heterogeneous agent model with measured expectations under different policy counterfactuals. We express the consumption of non-hand-to-mouth households as a function of expectations only and elicit all expectations appearing in the consumption functions for alternative policy scenarios with tailored surveys. Feeding these individual-level expectations into the model illustrates that a modest forward guidance statement in March 2021 would have reduced aggregate consumption by 0.14 percent on impact and an interest rate hike of 40 basis points in March 2022 would have reduced aggregate consumption by 0.30 percent on impact.
Keywords: D12; D14; D83; D84; E32; G11; 330; monetary policy; expectation formation; aggregate consumption